The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fnagi.2021.792840
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Basic Research for CSF1R-Microglial Encephalopathy

Abstract: Colony-stimulating factor-1 receptor-microglial encephalopathy is a rare rapidly progressive dementia resulting from colony-stimulating factor-1 receptor (CSF1R) mutations, also named pigmentary orthochromatic leukodystrophy (POLD), hereditary diffuse leukoencephalopathy with spheroids (HDLS), adult-onset leukoencephalopathy with axonal spheroids, and pigmented glia (ALSP) and CSF1R-related leukoencephalopathy. CSF1R is primarily expressed in microglia and mutations normally directly lead to changes in microgl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“… 24 CSF1R ‐related leukoencephalopathy is characterized by a predominant involvement of microglia, classifying as microgliopathy. 10 , 25 Approximately 95% of previously reported CSF1R variants linked to leukoencephalopathy are located within the TKD, leading to the impairment of autophosphorylation. In vitro experiments have shown that cells expressing mutant CSF1R fail to exhibit ligand‐induced autophosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“… 24 CSF1R ‐related leukoencephalopathy is characterized by a predominant involvement of microglia, classifying as microgliopathy. 10 , 25 Approximately 95% of previously reported CSF1R variants linked to leukoencephalopathy are located within the TKD, leading to the impairment of autophosphorylation. In vitro experiments have shown that cells expressing mutant CSF1R fail to exhibit ligand‐induced autophosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical reviews have focused on the diagnosis of adult leukodystrophies, and particularly on “microglial leukoencephalopathies” [ 198 , 199 , 200 ]. Hematopoietic stem cell transplantation has been used in a few clinical trials with variable results [ 110 , 199 , 201 , 202 , 203 , 204 ]. More specific attempts to treat CSF1R-microglial encephalopathy are focused on microglial-based therapies [ 205 ].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, PLOSL has been considered a primary microgliopathy [ 1 , 7 ]. Since microglia and osteoclasts are affected in NHD, redefinition of the disease as a multisystemic “immunological” disease has also been proposed [ 110 ]. Treatments directed only to microglia will be inefficient to cover the complex pathology in NHD.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, CSF1 and its receptor CSFR1, showed significant upregulation in microglia surrounding the Abeta plaques and as such, has been proposed as a marker of neurodegenerative diseases [90]. Likewise, Csf1 mRNA is increased in CSF1R-microglialencephalopathy or glia-original dementia, a rare autosomal dominant disease caused by mutations in the gene coding for CSF1R resulting in microglial dysfunction [184]. Finally, Csf1 transcripts were found to be upregulated in the ischemic hemisphere of a mouse model of stroke [86].…”
Section: Brain Macrophages Responses To Strokementioning
confidence: 99%